Wind turbine optimal site matching based on capacity and availability factors - Ghajar, R. (2017)
This paper introduces a simple method to enable the selection of the most appropriate wind turbine for given sites in which the values of the Weibull shape parameter k and scale parameter c are known. T he matching between site and turbine characteristics can be optimized by defining two important parameters: The capacity factor Cf, and the availability factor Af. Published wind data of 10 sites are used to perform site matching with a variety of commercially available wind turbine generators by evaluating the capacity factor, availability factor and annual energy output. T his study argues that the incorporation of the availability factor in the turbine-site matching process will have an added value in terms of lowering the overall electric energy production cost of the system due to the fact that although the energy required by system peaking units will remain the same, the number of start-ups and shutdown may be reduced.